High-resolution geostationary satellite observations of free tropospheric NO 2 over North America and implications for lightning emissions - Ruijun Dang; Daniel J. Jacob; Huiqun Wang; Caroline R. Nowlan; Gonzalo Gonzalez Abad; Heesung Chong; Xiong Liu; Viral Shah; Laura H. Yang; Yujin J. Oak; Eloise A. Marais; Rebekah P. Horner; et al. (Proceedings of the National Academy of Sciences, 2025)
Free tropospheric (FT) nitrogen dioxide (NO 2 ) plays a critical role in atmospheric oxidant chemistry as a source of tropospheric ozone and of the hydroxyl radical (OH). It also contributes significantly to satellite-observed tropospheric NO 2 columns, which should be considered when using these columns to quantify surface emissions of nitrogen oxide radicals (NO x ≡ NO + NO 2 ). But large uncertainties remain in the sources and chemistry of FT NO 2 because observations are sparse. Here, we construct a cloud-sliced FT NO 2 (700 to 300 hPa) product from the Tropospheric Emissions: Monitoring of Pollution (TEMPO) geostationary satellite instrument over North America. This product provides higher data density and quality than previous products from low Earth orbit instruments, including the first observations of the FT NO 2 diurnal cycle in different seasons. Combined with coincident observations from the Geostationary Lightning Mapper, the TEMPO data imply that lightning is the dominant source of FT NO x in nonwinter seasons. Comparison of TEMPO FT NO 2 data with the Goddard Earth Observation System-Composition Forecasts (GEOS-CF) atmospheric chemistry model shows overall consistent magnitudes, seasonality, and diurnal variation, with a midday minimum in nonwinter seasons from photochemical loss. However, there are major discrepancies that we attribute to GEOS-CF’s use of a standard cloud-top-height-based scheme for the lightning NO x source. We find that this scheme underestimates offshore lighting flash density and misrepresents the diurnal cycle of lightning over land. Our FT NO 2 product provides a unique resource for improving the lightning NO x parameterization in atmospheric models and the ability to use NO 2 observations from space to quantify surface NO x emissions.